Amphiphilic Peptoid‐Directed Assembly of Oligoanilines into Highly Crystalline Conducting Nanotubes. Issue 4 (17th January 2022) - Li, Zhiliang; Tran, Duyen K.; Nguyen, Mary; Jian, Tengyue; Yan, Feng; Jenekhe, Samson A.; Chen, Chun‐Long
Abstract: It is reported herein the synthesis of a novel amphiphilic diblock peptoid bearing a terminal conjugated oligoaniline and its self‐assembly into small‐diameter ( D ≈ 35 nm) crystalline nanotubes with high aspect ratios (>30). It is shown that both tetraaniline (TANI)‐peptoid and bianiline (BANI)‐peptoid triblock molecules self‐assemble in solution to form rugged highly crystalline nanotubes that are very stable to protonic acid doping and de‐doping processes. The similarity of the crystalline tubular structure of the nanotube assemblies revealed by electron microscopy imaging, and X‐ray diffraction analysis of the nanotube assemblies of TANI‐functionalized peptoids and nonfunctionalized peptoids showed that the peptoid is an efficient ordered structure directing motif for conjugated oligomers. Films of doped TANI‐peptoid nanotubes has a dc conductivity of ca. 95 mS cm −1, while the thin films of doped un‐assembled TANI‐peptoids show a factor of 5.6 lower conductivity, demonstrating impact of the favorable crystalline ordering of the assemblies on electrical transport. These results demonstrate that peptoid‐directed supramolecular assembly of tethered π ‐conjugated oligo(aniline) exemplify a novel general strategy for creating rugged ordered and complex nanostructures that have useful electronic and optoelectronic properties. Abstract : Peptoid‐directed supramolecular self‐assembly of π ‐conjugated oligoanilines into highly ordered, crystalline, and conducting nanotubes.